Efficacy of an alcohol-free chlorhexidine mouthrinse as an antimicrobial agent - Eldridge, Kathrine R.; Finnie, Sonja F.; Stephens, Joni A.; Mauad, Amable M.; Munoz, Carlos A.; Kettering, James D. (The Journal of prosthetic dentistry, 1998)
Statement of problem. Antimicrobial mouthrinses have become an important part of comprehensive dental care. However, mouthrinses that contain alcohol have been shown to be detrimental to patients undergoing radiation therapy for head and neck cancer, to some immunocompromised patients, to families with small children, and to persons sensitive to alcohol. Purpose. This study evaluated the effectiveness of alcohol-free, 0.12% chlorhexidine mouthrinse in reducing microbial levels when compared with commercially available 0.12% chlorhexidine (CHX) and essential oils mouthrinses. Material and methods. This study consisted of both in vitro and in vivo investigations. The double-blind study included 32 subjects randomly assigned to 3 groups, equalized according to the indices tested. One group (n = 11) received essential oils rinse; the second group (n = 11) received CHX; and the last group (n = 10) received the alcohol-free CHX. Subjects were asked not to use any mechanical means of oral hygiene for 21 days. The in vitro part of the study consisted of Streptococcus mutans strip tests. Results. Mean plaque scores for both CHX products decreased after 21 days, whereas the mean for the essential oils increased. Bleeding and gingival index scores for all 3 groups increased, which may be due to the initially healthy tissues of the participants. Relative microbial growth for S mutans for both the CHX products decreased to 0 after 21 days, whereas the counts for the essential oils group remained varied.(J Prosthet Dent 1998;80:685-90.)